Recurrent laryngeal nerve paralysis after thyroid cancer surgery and intraoperative nerve monitoring. (24th December 2018) - Mizuno, Kayoko; Takeuchi, Masato; Kanazawa, Yuji; Kitamura, Morimasa; Ide, Kazuki; Omori, Koichi; Kawakami, Koji
Abstract : Objectives/Hypothesis: This study aimed to investigate the risk of postoperative recurrent laryngeal nerve paralysis (RLNP) with and without the use of intraoperative nerve monitoring (IONM) during thyroid cancer surgery. Study Design: Retrospective cohort study. Methods: This study utilized a nationwide claims database in Japan. Patients who underwent thyroid cancer surgery with and without IONM were included, and postoperative RLNP incidence was compared. Results: The study included 5, 804 patients. Multivariable logistic regression analysis revealed that use of IONM was not associated with increased RLNP risk (odds ratio: 1.15; 95% confidence interval: 0.67‐1.96). There was no significant effect on RLNP prevention when stratified by tumor or nodal classification. Rather, the patients who had T4 or N1b classifications who received IONM had higher incidences of RLNP. Conclusions: Use of IONM did not significantly reduce the risk of RLNP. The results for the T4 and N1b populations may be explained by indication bias or unmeasured confounders. Level of Evidence: NA Laryngoscope, 129:1954–1960, 2019